MENYOAL KEADILAN SOSIAL TERHADAP JEMAAT AHMADIYAH DI INDONESIA PERSPEKTIF ISLAM DAN SILA KE-5 PANCASILA - Andi Muh. Taqiyuddin BN; Misbahuddin; Kurniati (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
The purpose of this research is to reveal the history of the emergence of Ahmadiyya and its entry into Indonesia, the facts of violence against the Ahmadiyya Congregation in Indonesia and the government's role in protecting the Ahmadiyya Congregation, as well as social justice for the Ahmadiyya Congregation in Indonesia in the perspective of Islam and Pancasila. This qualitative research is a library research that collects data through literature such as journals and books. The results show that Ahmadiyya is a faith-based organization initiated and propagated by Mirza Ghulām Ahmad. There are two sects within this organization; Lahore and Qadian. The Lahore Ahmadiyah sect was spread to Indonesia through Mirza Wali Ahmad and Maulana Ahmad in 1924. Meanwhile, the Ahmadiyah Qadian sect was spread by Rahmat Ali in 1925. The Lahore sect stated that Ahmadiyah was born in 1888 while the Qadian sect stated that Ahmadiyah was born the next year. The existence of the Ahmadiyya Congregation in Indonesia is marked by a series of episodes in the form of neglected facts of social justice. Various acts of attacks, violence, persecution, and so on are portraits of the life of the Ahmadiyya Muslim Community in Indonesia as legal citizens before the law. It is understandable that the government's role in protecting the Ahmadiyya Congregation has not been maximized due to various acts of violence against the Ahmadiyya Congregation in Indonesia. Based on the fifth precept of Pancasila and from an Islamic perspective, in this case the preservation of life, lineage, property and reason, social justice has not been realized for the Ahmadiyya Congregation in Indonesia with violent attacks in the form of indiscriminate acts. vigilantes against the Ahmadiyya Congregation are still found.